PERANCANGAN SISTEM INFORMASI PENGOLAHAN JADWAL MATA PELAJARAN SISWA SECARA ONLINE DI SMPN 31 PADANG BERBASIS WEB - Khairunisa Samosir; Darmansah Darmansah; Ni Wayan Wardani (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2020)
Today is the era of global information technology, where everything is done practically, accurately and up to date with information obtained from anywhere and anytime. Currently scheduling lessons at SMP NEGERI 31 Padang is still done manually by the curriculum section, with previously held a task division meeting with subject teachers. From determining the number of classes, the number of teachers in the school and the number of teaching hours for each teacher are still done manually. The allocation and determination of teachers is an important element in the preparation of subject schedules, but is also a common problem in the schedule preparation process. By building a web-based information system with PHP and MySql programming languages ​​and system modeling using UML (Unified Modeling Language), it is hoped that it can facilitate data processing for students, teachers, and student subject schedules so that fast, precise and accurate results can be obtained at SMP NEGERI 31. Padang.